1979
DOI: 10.1001/jama.1979.03290290030020
|View full text |Cite
|
Sign up to set email alerts
|

Subungual Squamous Cell Carcinoma

Abstract: Twelve patients with subungual squamous cell carcinoma were treated at Memorial Sloan-Kettering Cancer Center during a 27-year period. To our knowledge, only 58 cases are reported in the literature. Trauma and chronic infection were predisposing factors in some of the cases, and radiation therapy was a substantive predisposing factor in our series. Disarticulation of the distal phalanx proved effective in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…However, complete wide local excision of the tumour may be required to prevent recurrence, especially if there is evidence of local invasion [4], as bony involvement can be found in up to 20% of patients [12]. Our patient was referred promptly and underwent surgical excision due to the locally invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete wide local excision of the tumour may be required to prevent recurrence, especially if there is evidence of local invasion [4], as bony involvement can be found in up to 20% of patients [12]. Our patient was referred promptly and underwent surgical excision due to the locally invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…3,1214 Previously little was known about its etiology, and only arsenic exposure and radiation exposure were reported. 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Digits of the hand are involved more often than those of the feet. Typically, one digit is involved; however, some studies have reported on simultaneous involvement of multiple digits3. The thumb, particularly the distal phalanx, tends to be the most commonly affected digit3,4.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports in the literature, the duration of time from onset of a nail condition to diagnosis of squamous cell carcinoma varies greatly, from a few months to close to 35 years. Invasion of bone is found in approximately 20% of patients with subungual squamous cell carcinoma3. Metastasis and lymph node involvement is an atypical finding; however, it has been reported in a few cases.…”
Section: Discussionmentioning
confidence: 99%